Pre-service teachers training satisfaction and practical knowledge acquisition in artificial intelligence teachers training program: a multiple regression study - Song, Pu; Ahmad, Nor Aniza; Md Khambari, Mas Nida; Ng, Keng Yap; Chin, Wei Mun (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The acquisition of practical knowledge is the main objective in pre-service teachers (PSTs) training. However, research with the focus on the relationship between pre-service teachers’ training and practical knowledge acquisition through quantitative methods are limited. Additionally, the influence of various educational activities in pre-service teachers’ training on teachers' practical knowledge acquisition remains unclear. Hence, this study employed a multiple regression analysis to investigate pre-service teachers’ satisfaction who are in an artificial intelligence training program to predict practical knowledge acquisition. This study utilizes a dataset of 219 pre-service teachers from an artificial intelligence teachers’ training program at a university of Guizhou province. Findings from the multiple regression analysis indicated that pre-service teachers’ acquisition of practical knowledge are mainly influenced by three factors which are: (1) knowledge preparation, instructional design and reflection in the process of PSTs training, (2) teaching in primary school and (3) teamwork. Not only this study has implications on the training process of preservice teachers at the university but also in the cultivation of teachers’ practical knowledge.